Mysticism and the inner psyche in the novel Hilang Dalam Dekapan Semeru: A symbolic and psychological analysis - Zahwa Aliya Rastiani; Afita Putri Korindri; Mitha Adinda Kusumaningrum; Laili Fitroh Ramadhani; Elsa Fidah Evanda; Abdullah Al Fathin; Pribadi Priyo Hastomo; Onok Yayang Pamungkas (Journal of Language, Literature, Social and Cultural Studies, 2026)
This research focuses on the symbols of mysticism and the psychology of mysticism in the novel Hilang Dalam Dekapan Semeru (Aditya, 2025). Mystical symbols such as the figure of a woman dressed in white, frankincense, offerings, dolls, free-range chicken eggs, seven-faced flowers, and the mystical experiences of climbers are analysed in the real world and the supernatural world in Javanese culture. Each symbol has a meaning as a form of spiritual communication that reflects people's belief in the supernatural. The research method uses the analysis of content in the novel, with a systematic, objective, replicative technique approach to encode or categorize and interpret the text to find a specific pattern of meaning. This study also examines the psychology of climbers who experience mystical experiences such as changes in consciousness, anxiety, hallucinations, and extreme emotional responses. Transpersonal psychology can be called spiritual psychology, because it compares the spiritual and psychological experiences of humans. Mystical psychology research is related to transpersonal psychology that describes the character's experiences in the occult. These findings confirm that the novel contains symbols of mysticism and the psychology of mysticism, as well as spirituality between humans and the supernatural. This relationship also connects the supernatural world in the view of the Javanese people.